How Much Has Nepal Lost in the Last Decade Due to Load Shedding? : An Economic Assessment Using a CGE Model - Timilsina, Govinda (World Bank, Washington, DC, 2018)
Nepal suffered with severe shortage of electricity supply or load shedding in the last decade. Electricity load shedding is considered one of the major barriers to the country's economic development. This study uses a computable general equilibrium model to estimate the economic costs of electricity load shedding the country faced during 2008-16. The study shows that if there had been no load shedding, annual gross domestic product, on average, would have been almost 7 percent higher than it was during 2008-16. The worst effects of load shedding were on the investment environment. If there had been no load shedding, investment would have been 48 percent higher than it was. Although electricity load shedding has been reduced recently in the residential sector through better electricity load management and increased electricity production and imports, the industrial sector, one of the main sources of economic growth in the country, still faces load shedding. Unless the electricity load shedding is eliminated, Nepal will continue to suffer a heavy economic loss.